Update of the effect estimates for common variants associated with carotid intima media thickness within four independent samples: The Bonn IMT Family Study, the Heinz Nixdorf Recall Study, the SAPHIR Study and the Bruneck Study. (June 2016) - Geisel, Marie H.; Coassin, Stefan; Heßler, Nicole; Bauer, Marcus; Eisele, Lewin; Erbel, Raimund; Haun, Margot; Hennig, Frauke; Moskau-Hartmann, Susanna; Hoffmann, Barbara; Jöckel, Karl-Heinz; Kedenko, Lyudmyla; et al.
Abstract: Carotid intima media thickness (cIMT) is a marker for subclinical atherosclerosis. The most recent genome-wide association meta-analysis (GWAMA) from the CHARGE consortium identified four genomic regions showing either significant ( ZHX2, APOC1, PINX1 ) or suggestive evidence ( SLC17A4 ) for an association. Here we assess these four cIMT loci in a pooled analysis of four independent studies including 5446 individuals by providing updated unbiased effect estimates of the cIMT association signals. The pooled estimates of our four independent samples pointed in the same direction and were similar to those of the GWAMA. When updating the independent second stage replication results from the earlier CHARGE GWAMA by our estimates, effect size estimates were closer to those of the original CHARGE discovery. A fine-mapping approach within a ±50 kb region around each lead SNP from CHARGE revealed 27 variants with larger estimated effect sizes than the lead SNPs but only three of them showed a r 2  > 0.40 with these respective lead SNPs from CHARGE. Some variants are located within potential functional loci. Highlights: Estimates from association studies can be biased due to the "winner's curse". We validated the cIMT loci reported by the CHARGE consortium in four studies. We address the winner's curse and present unbiased estimates for these loci. We performed a fine-mapping in 100 kb around each CHARGE top hit. Independent variants around each CHARGE lead SNP showed larger effects.